Simple room-temperature preparation of high-yield large-area graphene oxide - Huang NM (Dove Medical Press, 2011)
NM Huang1, HN Lim2, CH Chia3, MA Yarmo4, MR Muhamad51Low Dimensional Materials Research Centre, Physics Department, University of Malaya, Kuala Lumpur, Malaysia; 2Centre for Ionics University of Malaya, Physics Department, University of Malaya, Kuala Lumpur, Malaysia; 3School of Applied Physics, Faculty of Science and Technology, Universiti Kebangsaan, Malaysia; 4School of Chemical Sciences and Food Technology, Faculty of Science and Technology, Universiti Kebangsaan, Malaysia; 5Chancellery Office, Multimedia University, Jalan Multimedia, Selangor Darul Ehsan, MalaysiaAbstract: Graphene has attracted much attention from researchers due to its interesting mechanical, electrochemical, and electronic properties. It has many potential applications such as polymer filler, sensor, energy conversion, and energy storage devices. Graphene-based nanocomposites are under an intense spotlight amongst researchers. A large amount of graphene is required for preparation of such samples. Lately, graphene-based materials have been the target for fundamental life science investigations. Despite graphene being a much sought-after raw material, the drawbacks in the preparation of graphene are that it is a challenge amongst researchers to produce this material in a scalable quantity and that there is a concern about its safety. Thus, a simple and efficient method for the preparation of graphene oxide (GO) is greatly desired to address these problems. In this work, one-pot chemical oxidation of graphite was carried out at room temperature for the preparation of large-area GO with ~100% conversion. This high-conversion preparation of large-area GO was achieved using a simplified Hummer’s method from large graphite flakes (an average flake size of 500 µm). It was found that a high degree of oxidation of graphite could be realized by stirring graphite in a mixture of acids and potassium permanganate, resulting in GO with large lateral dimension and area, which could reach up to 120 µm and ~8000 µm2, respectively. The simplified Hummer’s method provides a facile approach for the preparation of large-area GO.Keywords: graphene oxide, simplified Hummer’s method, chemical oxidation